Միջմշակութային իրազեկության ձևավորման հայեցակերպերը - Նարինե Հարությունյան (ՀՀ ԳԱԱ հրատ.)
Cross-cultural communication misunderstandings happen all the time.Unfortunately there isn’t a way to avoid them. But with the adequate skills you can limit these misunderstandings. Therefore, it has become useful to know about cross-cultural competence.
Keywords: Philology; Linguistics; Language and Literature